Edukasi Pengelolaan Uang Jajan Melalui Literasi Keuangan dalam Meningkatkan Berinvestasi dan Menabung - Eka Sariningsih; Ananda Ramadya Rahmatina; Annadya Kirani; Elza Nur Annisya; Rahma Agustia (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2026)
Purpose: This community service activity was conducted to improve financial literacy among high school students through education on pocket money management. The program was implemented at SMA Negeri 2 Kalianda, South Lampung Regency, targeting students in grades XI and XII. The main problems identified were the low level of students’ awareness in managing pocket money and the lack of saving and investing habits from an early age. Through this program, participants were introduced to basic financial literacy concepts, wise pocket money management, and simple strategies for saving and investing. The implementation methods included interactive lectures, pocket money management simulations, group discussions, and learning evaluations using pre-tests and post-tests. The results showed a significant improvement in students’ financial literacy, with 85% of participants correctly answering questions related to basic financial concepts after the activity, and more than 70% expressing motivation to save regularly. This program successfully fostered healthy financial habits and increased awareness of personal financial management among students. Methodology: The implementation of this community service program employed an educational and participatory approach. The activity began with a pre-test to assess students’ initial understanding of financial literacy. The material was then delivered through interactive lectures covering financial literacy concepts, the importance of pocket money management, and an introduction to saving and simple investment. To enhance students’ understanding, pocket money management simulations and group discussions were conducted. The program concluded with a post-test to evaluate the improvement in participants’ financial literacy after the activity. Results: The results of the program indicated a significant improvement in students’ understanding of financial literacy. Based on the post-test results, 85% of participants were able to correctly answer questions related to basic financial concepts. In addition, more than 70% of students expressed motivation to start saving regularly and to manage their pocket money more wisely. Active participation during discussions and simulations also reflected increased awareness of the importance of financial planning from an early age. Conclusion: This community service activity successfully improved the financial literacy of students at SMA Negeri 2 Kalianda. The program increased students’ awareness of the importance of pocket money management, encouraged saving habits, and introduced the basics of simple investment that can be applied from school age. Therefore, this activity made a positive contribution to fostering healthy financial behavior among high school students. Limitation: The limitations of this program include the relatively short duration of implementation, which limited the depth of material delivered. In addition, the program did not include long-term mentoring to monitor the sustainability of changes in students’ financial behavior. Contribution: This program contributes to improving students’ financial literacy by introducing practical pocket money management and encouraging early saving and simple investment habits among high school students.